Cognitive Performance in Early-Onset Schizophrenia and Attention-Deficit/Hyperactivity Disorder: A 25-Year Follow-Up Study - Øie, Merete G.; Sundet, Kjetil; Haug, Elisabeth; Zeiner, Pål; Klungsøyr, Ole; Rund, Bjørn R. (Frontiers in Psychology, 2021)
Early-Onset Schizophrenia (EOS) and Attention Deficit-Hyperactivity Disorder (ADHD) are early- onset neurodevelopmental disorders associated with cognitive deficits. The current study represents the first attempt to compare these groups on a comprehensive cognitive test battery in a longitudinal design over 25 years in order to enhance our knowledge of particular patterns resulting from the interaction between normal maturational processes and different illness processes of these disorders. In the baseline study, 19 adolescents with schizophrenia were compared to 20 adolescents with ADHD and 30 healthy controls (HC), all between 12 and 18 years of age. After 13 years (T2) and after 25 years (T3) they were re-evaluated with the cognitive test battery. A cognitive Composite Score was used in a linear mixed model. The EOS group had a significant cognitive stagnation or deterioration from T1 to T2 compared to HC. However, the EOS group had the most positive change from T2 to T3, supporting a stable level of cognitive performance over the 25 year span. The ADHD group improved or had similar development as the HC group from T1 to T2. They continued to improve significantly compared to the HC group from T2 to T3. Individuals in the EOS group performed more impaired on the cognitive composite score compared to the HC group and the ADHD group at all three time points. Results might indicate a neurodevelopmental pathway of EOS with subnormal cognitive development specific in adolescence. In comparison, the ADHD group had a more consistent cognitive maturation supporting a maturational delay hypothesis of ADHD